Analysis of Profitability by Implementing RFID-Technology in 3PL Warehouse Business - Andrea Mayer (Journal of Applied Leadership and Management, 2016)
Facing the dynamic field of warehouse logistics and the rising customer process demands combined with cost pressure then a constant change management and continuous, customer-oriented improvement process must take place in 3PL warehouse business. Hence technological change, especially in regards of automatic object localisation and product tracking along the supply chain, gains in importance. That raises the question if a change from barcode technology to radio frequency identification generates profitability in 3PL warehouse business
Keywords: 650; RFID; 3PL; warehouse business; barcode technology; raio frequency; warehouse logistics